Hydrogen co-firing simulation for emission reduction and efficiency in an 880 MW combined cycle power plant - Mulyadi, Eka Octaviyatna; Wulan, Praswasti PDK (Politeknik Negeri Lhokseumawe, 2025)
This study evaluates the environmental and performance impacts of hydrogen co-firing with natural gas in an 880 MW Combined Cycle Power Plant (CCPP) in Jakarta, Indonesia. CO₂ emissions were estimated using the IPCC Tier-2 Method, while Aspen Plus simulation analyzed combustion performance under 10% and 20% hydrogen blending. Fuel composition was determined through Gas Chromatography analysis and processed using a weighted average method. The results show that hydrogen blending significantly reduces CO₂ emissions to approximately 10% at 10% hydrogen and 20% at 20% hydrogen, equivalent to 409,420 tons annually. NOₓ emissions increased moderately, by about 2.16% at 20% hydrogen, due to higher flame temperatures, yet remained far below regulatory limit of 400 mg/Nm³. Thermal efficiency improved from 54.08% (baseline) to 56.88% and 60.06% with 10% and 20% hydrogen, respectively, although net power output slightly declined. These findings highlight the role of hydrogen as a transitional energy carrier, capable of decarbonizing gas-fired power plants while improving efficiency with manageable environmental trade-offs. Although the study is based on steady-state simulations without pilot-scale validation, the integration of actual operational data strengthens its applicability. Hydrogen co-firing presents a technically viable pathway for reducing CO₂ emissions in the power sector.